Students' Attitude in Joining English Course at SMAN 2 Painan - Indah, Sri Mayang; Ramadhani, Syafitri (Journal of English Language Teaching, 2024)
This research was conducted to determine students' attitude in joining English course. The researcher used descriptive quantitative methods with questionnaire to get answers about students’ attitude. The purpose of this study is to find out what students' attitudes towards joining English courses are. The sample of this research was 30 students at SMAN 2 Painan. There were 30 statements that students had to fill in by choosing answers between strongly agree, agree, disagree, and strongly disagree. The findings show that of the 30 students who were sampled for the English course, most students gave a positive attitude in attending the English course. In particular, the positivity of the cognitive component with ten statements with an average of 3.30 (82.50%), the positivity of the affective component with eight statements with an average of 3.15 (78.85%), and the positivity of statements regarding conative component with twelve statements with an average of 3.18 (79.51%). From the results of this research, it can be concluded that students' attitude in joining English course based on the three components which are cognitive, affective, and conative reveal a positive attitude. Through this research, the findings also concluded that English courses have many benefits, especially for students who have joined English course in improving their English.